Banking for the Unbanked: The Promises, Pitfalls and Potentials of Mobile Banking - Fiocco, Melissa (Université d'Ottawa | University of Ottawa, 2019)
Over the past decade, we have witnessed a global effort to expand financial access to the unbanked and increase their capacity to securely store and transfer currency, take out loans and buy insurance. Mobile money was first created to respond to the demand for affordable and accessible financial services. It was quickly proclaimed the solution for financial exclusion in the global south, largely because of its tremendously successful implementation in East-Africa. Mobile money users, specifically those living in rural areas in Kenya, reported an amplified ability to mitigate financial risks and economic shocks after adopting the mobile service because it allowed them to access financial support from a more extended social network. As conflicting results emerged from studies which focused on the adoption, usage and impact rates of poor and vulnerable populations and those living in fragile and conflict-affected states, many researchers began to express doubts over the real value of mobile money. Efforts to expand mobile banking in other countries were mostly unsuccessful, specifically in states which lack a remittance-based economy, moderate human capital levels, robust financial institutions and telecommunication infrastructure. This is particularly evident in Afghanistan where poor infrastructure and low public trust in the banking sector contributed to subpar adoption rates, even though the high demand for affordable and accessible financial services is comparable to Kenya. Even in countries which share these characteristics, adoption, usage and impact rates of mobile banking have varied across population groups. Often, the poorest and most vulnerable populations, most notably the poorest 40% and low-income women, have either not experienced the same degree of financial inclusion or have been entirely excluded from this progress. This is primarily because many determinants of financial inclusion (gender, income level, urban-rural divide, and level of educational attainment) do not merely recede following the adoption of mobile money, but require more robust policy-changes, institutionstrengthening and infrastructure-building initiatives, and broader social change to be alleviated. Mobile money is not a band-aid solution to financial exclusion, but a tool which can contribute to bringing universal financial inclusion.